Tindak Tutur Ekspresif Penderita Down Syndrome Latih (Studi Kasus Syarifah Di SLB Negeri 1 Alahan Panjang) - Mulyani, Desri Mulyani; Dwinitia, Suci; Tiawati R, Refa Lina (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2023)
This study aims to describe the forms of expressive speech acts of people with Down syndrome. The type of research conducted in this research is qualitative. The method used in this research is descriptive analysis method. This research was conducted at SLB Negeri 1 Alahan Panjang, Lembah Gumanti sub-district, Solok Regency, West Sumatra Province. This research is focused on Syarifah's speech acts in SLB Negeri 1 Alahan Panjang. The main informant in this study is Syarifah because she is a patient with Down syndrome. The data collection technique uses the proficient method. The data validation technique uses triangulation. Data analysis techniques Data analysis using the Miles and Huberman (2014) model consists of data reduction, presentation of informal data, and drawing conclusions. The results of this study are five analyzes of expressive speech acts, including: 1) thanking, 2) congratulating, 3) forgiving, 4) blaming, and 5) praising.